Самовиховання медіаграмотності в умовах війни: двостороння проблематика та профілактика - Кожем’якіна, Ірина Віталіївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The war in Ukraine has been going on since 2014. In addition to hostilities and human casualties, this war poses a threat to the country’s information security. Russian aggression is aimed not only at an armed attack, but also at informational propaganda and hacker attacks. One of the main directions of Russian propaganda is creating the image of the “enemy” in the person of Ukraine and its Western partners. Russian media outlets spread fake news to make Ukrainians believe that their country is unstable and unable to protect its borders.